Impure HopesCRISPR and an HIV cure - Kirksey, E (Duke University Press, 2021)
The experiment in China that produced the world's first babies with “edited” DNA comes out of an international research program aimed at producing an HIV cure. An atmosphere of secrecy surrounded this experiment at the edge of the law. Volunteers who signed up for the experiment were HIV‐positive tonzghi—gay and bisexual “comrades” already living with closely guarded secrets and conflicted desires. Impure hopes—a mix of heterosexual dreams about reproductive futurity and biotech speculation about an HIV cure—drove the research forward. Volunteers were caught between dreamworlds, harboring hopes that were not entirely their own. The story of these patients is tangled up with CRISPR, a fast and cheap tool for manipulating DNA that contains tantalizing promises of medical breakthroughs for innovators and investors. Speculation in the innovation economy produced an earlier gene‐editing experiment in the United States that brought HIV‐positive veterans of ACT UP together with biotechnology entrepreneurs. After achieving promising results, a fickle market pushed gene‐editing enterprises away from HIV cure research. Building on earlier work about impure science, this article makes an argument against purity to consider the contours of hope in ethically compromised times. Hope demands ongoing articulation work. As powerful political and economic forces threaten to steal queer hopes or simply capitalize on them, it is important to make our own ethical, political, and discursive cuts—to selectively renew some articulations while breaking other connections.